English as an Agent of Change in India - Mittapalli, Rajeshwar (University of Colombo, 2015)
In this presentation I will take a historical, sociological and economic view of language rather than a linguistic view. I think even the theme of this conference warrants such a view. For the sake of convenience of presentation I have divided my talk into two parts. In the first part, I will dwell on the importance of language in general and how it has always played a significant role in shaping and transforming society. In the second part, I will go into how English acted as an agent in the social, political, economic, linguistic and even spiritual transformation of India; how it brought about cultural integration; and how it transformed the image of India in the world. I will conclude by making some pertinent observations on how, despite its enormous contribution, English is under attack from various quarters within India, and what could be done in response to these attacks so that English will continue to play its transformative role.
Keywords: English as an Agent of Change in India